New evidence on fund performance in extreme events - Mansor, Fadillah; Al Rahahleh, Naseem; Bhatti, M. Ishaq (Emerald, 2019)
Purpose: The purpose of this paper is to compare the return performance and persistence of ethical and conventional mutual funds during two extreme events, the Asian and the global financial crises under Shariah constraints. Design/methodology/approach: The overall sample comprises of 129 Islamic mutual funds (IMFs) and 350 conventional mutual funds (CMFs) in Malaysia, and the average monthly data cover two periods of market cycles, before and during a financial crisis. The net of all expenses data is obtained from the Morningstar Database. This study employs various market risk-adjusted performance measures (ratios) to estimate the funds’ overall performance during the crises, and then it uses CAPM model to estimate the parameters via panel data approach. Moreover, paper employs the two persistence performance measures on IMFs and CMFs through contingency tables. It tests for the performance persistence effects for IMFs, CMFs using repeat winner and the cross-product ratio (CPR) tests proposed by Malkiel (1995) and Brown and Goetzmann (1995), respectively. Findings: The main findings of the paper are: on average, both funds IMF and the CMF outperform the market return during the entire sample period; none of the funds is better than the “others” during the financial crises and the pre-crisis periods; the ethical fund – IMF outperforms the CMF over the study period. This outcome also indicates that ethical funds are more persistent especially during and the pre-crisis AFC and the GFC periods. Research limitations/implications: The finding of this study is limited to only Malaysian data because the objective was to guideline investors and market players in Malaysia to prefer investing in Islamic ethical funds to diversify their investment portfolio. Practical implications: Cautions to use existing ratio measures and CAPM model rather persistence measures may be used with existing methodologies in light of extreme events which influenced investor decision making for better returns at lower risks. Social implications: A class of ethical funds consists of religious sustainable, socially responsible and impact-investing (SRI) funds but Shariah implications of halal investment must be observed to avoid prohibited practices within the class of SRI funds. Originality/value: The work done in this paper are original in the sense that the authors employed various ratios to measure fund performance in conjunction with CAPM model and then tested for two persistence performance measures; the repeat winner and CPR tests. © 2019, Emerald Publishing Limited.